The Influence of Brand Image and Online Promotion on Purchase Decisions of Kopi Kenangan in Depok City - Naufal Raihan Aditama; Alfi Maghfuriyah; Febria Anjara (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the influence of Brand Image and Online promotion on purchasing decisions for Kopi Kenangan in Depok City, both partially and simultaneously. This research uses a quantitative approach method with an instrument in the form of a Likert-scale questionnaire. Data was collected through questionnaires distributed to 150 Kopi Kenangan consumers in Depok City as a sample. Data analysis used multiple linear regression. The sampling technique used non-probability sampling with purposive sampling and Malhotra methods. Data analysis was carried out using Statistical Program for Social Science (SPSS) version 27. The results showed that Brand Image (X1) and Online promotion (X2) both partially and simultaneously have a positive and significant effect on purchasing decisions (Y). The coefficient of determination value indicates that both independent variables contribute 70%, while the remaining 30% is influenced by other variables outside this study.